Sustainable management in COVID-19 times - Alvarez-Risco, Aldo; Rosen, Marc A.; Del-Aguila-Arcentales, Shyla (Advanced series in management ;, 2023)
COVID-19 has demanded management innovations across all sectors. As urban systems are made more sustainable, and our focus shifts towards the Circular Economy, this timely book sheds new light on emerging issues. Contributions to this volume highlight developments in: smart cities and urban innovation and resilience; building and re-building cross-culturally sustainable tourism and recreation; new international business models in a digitally transforming world; how digital tools are being used to promote STEM education in the 'new normal' post-2020 world; food insecurity and energy policy in Latin America; the role of leadership in teleworking and job satisfaction in the Asia-Pacific region; economic and socio-cultural impacts of recreational activities affected by COVID-19; entrepreneurship in COVID-19 times; and the integration of the UN Sustainable Development Goals in higher education institutions. Presenting new, innovative conceptualizations and viewpoints on management, Sustainable Management in COVID-19 Times explores a range of concepts that give insights into our post-pandemic world.